IL-17 inhibitor-associated inflammatory bowel disease: A study based on literature and database analysis - Deng, Zhenzhen; Wang, Shengfeng; Wu, Cuifang; Wang, Chunjiang (Frontiers in Pharmacology, 2023)
Objective: Few real-world studies have shown clear association between interleukin (IL)-17 inhibitors and inflammatory bowel disease (IBD) onset. This study investigated the reporting prevalence and evaluated the clinical features and management of IL-17 inhibitor-related IBD events. Methods: We used the US FDA Adverse Event Reporting System database and retrieved data, from 2015 to 2022, on IL-17 inhibitors to identify gastrointestinal inflammatory events and conduct disproportionality analyses by estimating the reporting odds ratios (RORs) and corresponding 95% confidence intervals (CIs). Furthermore, case reports and case series, from 2015 to 30 November 2022, on IBD induced by IL-17 inhibitors were collected for retrospective analysis. Results: A total of 388 cases of primary suspected IL-17 inhibitor-associated gastrointestinal events were reported (268 IBD and 120 colitis), including 348 cases involving secukinumab (SEC), 36 cases involving ixekizumab (IXE), and 4 cases involving brodalumab (BRO). Statistically significant reporting rates of total IBD events were observed for SEC and IXE (ROR = 2.13, 95% CI [1.96-2.30] and ROR = 2.79, 95% CI [2.39-3.27], respectively), whereas BRO did not trigger a safety signal. Twenty-nine studies, which included 34 cases, showed evidence of IBD, following SEC (79.4%) and IXE (20.6%) treatment. The median age was 42 years; typical initial symptoms included diarrhea (90.9%), abdominal pain (57.6%), bloody diarrhea (51.5%), and fever (36.4%). The median time to onset of IBD symptoms was 2.9 months. Some cases were accompanied by elevated white blood cell (WBC) count (87.5%), erythrocyte sedimentation rate (ESR; 85.7%), C-reactive protein (CRP; 100%), and fecal calprotectin (FC; 100%). Cessation of IL-17 inhibitors plus treatment with corticosteroids and TNF antagonists, as either monotherapy or in combination, could lead to complete clinical remission. The median time to remission after IL-17 inhibitor discontinuation was 4 weeks. Conclusion: IL-17 inhibitor treatment is associated with exacerbation and new onset of IBD and colitis. Obtaining a detailed patient history before initiation of treatment and monitoring gastrointestinal symptoms and intestinal inflammatory biomarkers during IL-17 inhibitor treatment is important for safe use of these drugs.